Bilateral Diabetic Knee Neuroarthropathy in a Forty-Year-Old Patient. (7th September 2016) - Goetti, Patrick; Gallusser, Nicolas; Borens, Olivier
Abstract : Diabetic osteoarthropathy is a rare cause of neuropathic joint disease of the knee; bilateral involvement is even more exceptional. Diagnosis is often made late due to its unspecific symptoms and appropriate surgical management still needs to be defined, due to lack of evidence because of the disease's low incidence. We report the case of a forty-year-old woman with history of diabetes type I who developed bilateral destructive Charcot knee arthropathy. Bilateral total knee arthroplasty was performed in order to achieve maximal functional outcome. Follow-up was marked by bilateral tibial periprosthetic fractures treated by osteosynthesis with a satisfactory outcome. The diagnosis of Charcot arthropathy should always be in mind when dealing with atraumatic joint destruction in diabetic patients. Arthroplasty should be considered as an alternative to arthrodesis in bilateral involvement in young patients.